CONVERTED WAVES REVEAL A THICK AND LAYERED TECTOSPHERE BENEATH THE KALAHARI SUPER-CRATON - Wittlinger G.; Farra V. (My University, 2007)
Thick and high-velocity roots are generally observed beneath the Archean cratons. Inside these high-velocity keels, velocity contrasts are detected neither by surface nor by body waves tomographies. We present here evidences based on the S-to-P and P-to-S converted waves for the existence of an irregularly stratified and thick keel beneath the Kalahari super-craton. To satisfy surface wave data and S-to-P conversions, the velocity model should have beneath the Moho a ~ 160 km thick anisotropic structure with vertical slow axis and decreasing anisotropic parameters with depth. Such a structure may stem from the preferred orientation of olivine [100] axis in the horizontal plane under shearing deformation. This structure, together with the ~ 100 km thick layer underlying it, forms a ~ 300 km thick continental root beneath the cratons. Inside this root, the P and S velocities should be higher on average respectively by an amount of 6% and 4% than the AK135 velocity model. Beneath ~ 300-350 km depth, a low velocity zone is clearly detected that may be either the remainder of large magma reservoirs related to cratonic flood basalts or a melted silicate layer created by the transformation, just above the 410-km deep discontinuity, of wadsleyite assembly to olivine assembly. © 2006 Elsevier B.V. All rights reserved.
Keywords: KALAHARI CRATON TECTOSPHERE; S AND P-RECEIVER FUNCTIONS IMAGING; Archean; Precambrian::Archean; Докембрий::Архей